POTENSI DESA SINTUNG SEBAGAI DESA WISATA DI LOMBOK TENGAH - Eka Purnama Bagaswara; Muh. Ilham H; Surayyal Hizmi (Juremi: Jurnal Riset Ekonomi, 2024)
This research aims to identify the Potential of Sintung Village as a Tourism Village in Central Lombok, using a SWOT analysis approach. This research uses a qualitative descriptive method, coupled with a data collection process carried out by observation, interviews, and documentation. The data used were primary data and secondary data. Data obtained from interviews with the management of Taman Sintung Tourism Village and supported by data from research journal references. The result of this research is that Taman Sintung Tourism Village has potential as a Tourism Village supported by completed development, adequate amenity and accessibility, and a strategic area, but still has many shortcomings that have not been resolved until now